2019
DOI: 10.29244/medkon.24.3.261-268
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Arbuscular Mycorrhizae Fungi from Rhizosphere of Daemonorops draco Blume in Jambi

Abstract: The research was conducted with the aim to analyze the diversity of arbuscular mycorrhizae fungi (AMF) from rhizosphere of Daemonorops draco Blume in Jambi. The sampling technique of soil and roots were done by propotional method. Sampling of the soil was carried out compositively at a depth of 0-20 cm and 20-40 cm, soil samples taken from jernang rhizosphere about 500 gram on each stem. Spores were isolated by wet filter pouring technique and continued with centrifugation, then the density of spores was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Soil microorganisms utilize Sub-optimal and infertile soils to aid plant growth by providing and absorbing plant nutrients, namely phosphorus (P) and micro-elements. The presence of AMF found in the ground can help the plants continue to grow despite the poor soil conditions (Purwati et al 2019). Furthermore, the results of soil sample analysis obtained a high C-organic content of 5.49%, which is likely to affect the number of AMF spores and the percentage of root infections by AMF.…”
Section: Resultsmentioning
confidence: 99%
“…Soil microorganisms utilize Sub-optimal and infertile soils to aid plant growth by providing and absorbing plant nutrients, namely phosphorus (P) and micro-elements. The presence of AMF found in the ground can help the plants continue to grow despite the poor soil conditions (Purwati et al 2019). Furthermore, the results of soil sample analysis obtained a high C-organic content of 5.49%, which is likely to affect the number of AMF spores and the percentage of root infections by AMF.…”
Section: Resultsmentioning
confidence: 99%
“…and Gigaspora sp. (Purwanti et al, 2019) and MycoSilvi consist of AMF Glomus mosseae + Acaulospora sp. and Gigaspora margarita (Budi et al, 2020) in the planting hole around the plant roots.…”
Section: Discussionmentioning
confidence: 99%
“…Root colonization is a sign of AMF symbiosis in plants with the presence of AMF structures such as spores, internal hyphae, external hyphae, vesicles and arbuscules on the host roots [12]. The AMF colonization on plant roots varies, and is influenced by various factors, including the species of the host plant [13] and soil chemical conditions, especially phosphorus availability [14]. Previous research has shown that AMF forms colonization with roots of various mangrove species, such as Agalia cuculata (73,33%), Heritiera fomes (52.74%), Sonneratia apetala (47.91%), Avicennia officinalis (37.5%), Bruguiera gymnorrhiza (23.33%), Aegiceras corniculatum (18.51%) [15], Avicennia marina (20% -32.5%), Bruguiera cylindrica (17.5% -27.5%), and Rhizophora stylosa (15% -37.5%) [16], however, there is no information on the association between AMF and A. lanata.…”
Section: Introductionmentioning
confidence: 99%